Cardamine hirsuta: a comparative view. (August 2016) - Hay, Angela; Tsiantis, Miltos
Abstract : Current advances in developmental genetics are increasingly underpinned by comparative approaches as more powerful experimental tools become available in non-model organisms. Cardamine hirsuta is related to the model plant Arabidopsis thaliana and comparisons between these two experimentally tractable species have advanced our understanding of development and diversity. The power of forward genetics to uncover new biology was evident in the isolation of REDUCED COMPLEXITY, a gene which is present in C. hirsuta but lost in A. thaliana, and shapes crucifer leaf diversity. Transferring two Knotted1-like homeobox genes between C. hirsuta and A. thaliana revealed a constraint imposed by pleiotropy on the evolutionary potential of cis regulatory change to modify leaf shape. FLOWERING LOCUS C was identified as a heterochronic gene that underlies natural leaf shape variation in C. hirsuta .